Continuous Extraction and Stripping of Neptunium By Fresh and Degradated Tributyle Phosphate Using Co-60 Cell - Al-Taweel, H. H.; Al-jibori, A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The behaviour of Np-239 during the Continuous extraction and stripping was followed . Three Continuous extraction experiments were carried out . In the first experiment the extraction and stripping were carried out by using Tributyl Phosphate / treated odorless kerosene as the organic phase , while the aqueous phase was uranium and neptunium-239 dissolved in 3M HNO3 . In the second experiment irradiation of organic phase up to 30 M rad were carried out , while keeping the aqueous phase as it is in the first experiment. In the third experiment , the acidity of the aqueous phase was 1.5M instead of 3M and keeping the organic phase as it is in experiment 1. The results obtained in tables 1-3 show the possibility of rejection Np-239 according to the conditions of run 1. The degradation product of the tributyl phosphate namely di and monobutyl phosphate plays an important role in the difficulty of Np stripping. The third experiment conditions were the best.